SUZUKI-TYPE FIXED POINT THEOREMS FOR TWO MAPS IN METRIC-TYPE SPACES - Dung, N. V.; Thanh Ly, N. T.; Thinh, V. D.; Hieu, N. T. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this paper, we generalize the Suzuki-type fixed point theorems in [N. Hussain, D.Doric, Z.~Kadelburg, and S.~Radenovic, Suzuki-type fixed point results in metric type spaces, Fixed Point Theory Appl 2012:126 (2012), 1 - 10] for two maps on metric-type spaces. Examples are given to validate the results.